Distinct roles of PI3Kδ and PI3Kγ in a toluene diisocyanate-induced murine asthma model. (30th April 2021) - Xu, Caiyun; Chen, Shuyu; Deng, Yao; Song, Jiafu; Li, Jiahui; Chen, Xin; Chang, Ping; Yao, Lihong; Tang, Haixiong
Abstract: TDI-induced asthma is characterized by neutrophil-dominated airway inflammation and often associated with poor responsiveness to steroid treatment. Both PI3Kδ and PI3Kγ have been demonstrated to play important proinflammatory roles in ovalbumin-induced asthma. We've already reported that blocking pan PI3K effectively attenuated TDI-induced allergic airway inflammation. Yet the specific functions of PI3Kδ and PI3Kγ in TDI-induced asthma are still unclear. Male BALB/c mice were first dermally sensitized and then challenged with TDI to generate an asthma model. Sellective inhibitors of PI3Kδ (IC-87114, AMG319) and PI3Kγ (AS252424, AS605240) were respectively given to the mice after each airway challenge. Treatment with IC-87114 or AMG319 after TDI exposure led to significantly decreased airway hyperresponsiveness (AHR), less neutrophil and eosinophil accumulation, attenuated airway smooth muscle (ASM) thickening, less M1 and M2 macrophages in lung, as well as lower levels of IL-4, IL-5, IL-6 and IL-18 in bronchoalveolar lavage fluid (BALF) and recovered IL-10 production. While mice treated with AS252424 or AS605240 had increased AHR, more severe ASM thickening, larger numbers of neutrophils and eosinophils, more M1 but less M2 macrophages, and higher BALF levels of IL-4, IL-5, IL-6, IL-10, IL-12, IL-18 when compared with those treated with vehicle. These data revealed that pharmacological inhibition of PI3Kδ attenuates TDI-induced airway inflammation while PI3Kγ inhibition exacerbates TDI-induced asthma, indicating distinct biological functions of PI3Kδ and PI3Kγ in TDI-induced asthma.